A Retrospective Case-Control Study Evaluating the Bowel Preparation Quality during Surveillance Colonoscopy after Colonic Resection. (6th March 2014) - Pontone, Stefano; Leonetti, Giovanni; Lamazza, Antonietta; Fiocca, Fausto; Filippini, Angelo; Fanello, Gianfranco; Cereatti, Fabrizio; Fiori, Enrico; Angelini, Rita; Patrizi, Gregorio; Brighi, Manuela; Vetere, Simone; et al.
Abstract : Purpose. Bowel preparation for surveillance endoscopy following surgery can be impaired by suboptimal bowel function. Our study compares two groups of patients in order to evaluate the influence of colorectal resection on bowel preparation. Methods. From April 2010 to December 2011, 351 patients were enrolled in our retrospective study and divided into two homogeneous arms: resection group (RG) and control group. Surgical methods were classified as left hemicolectomy, right hemicolectomy, anterior rectal resection, and double colonic resection. Bowel cleansing was evaluated by nine skilled endoscopists using the Aronchick scale. Results . Among the 161 patients of the RG, surgery was as follows: 60 left hemicolectomies (37%), 62 right hemicolectomies (38%), and 33 anterior rectal resections (20%). Unsatisfactory bowel preparation was significantly higher in resected population (44% versus 12%; P  v a l u e = 0.000 ). No significant difference (38% versus 31%, P  v a l u e = n s ) was detected in the intermediate score, which represents a fair quality of bowel preparation. Conclusions. Our study highlights how patients with previous colonic resection are at high risk for a worse bowel preparation. Currently, the intestinal cleansing carried out by 4 L PEG based preparation does not seem to be sufficient to achieve the quality parameters required for the post-resection endoscopic monitoring.